Pengembangan Media Frogmath Untuk Operasi Penjumlahan Pada Siswa Tunagrahita Ringan Kelas VI Di UPT SLB Negeri 1 Selayar - Ria Istianingsih; Hadis, Abdul; Zulfitrah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The problem examined in this research is motivated by the need for media that can support the learning process of addition operations. Furthermore, sixth-grade students with mild intellectual disabilities were found to experience academic difficulties, particularly in solving addition problems. The research problem is formulated as follows: The results of the needs analysis, development phase, prototype, validity, and effectiveness of Frogmath media for addition operations for students with intellectual disabilities. This study aims to determine the results of the needs analysis, development phase, prototype, validity, and effectiveness of Frogmath media for addition operations for students with mild intellectual disabilities. This study applies the 4-D development model (Four-D Model), which consists of four stages: definition, design, development, and dissemination. The results are as follows: (1) The needs analysis shows that sixth-grade students with intellectual disabilities require Frogmath media that has an attractive and interactive appearance to encourage students to learn more; (2) The development stage begins with the definition, design, and development stages. In this development research, it only reaches development. (3) The designed prototype of the frogmath media is used to provide an initial visual representation before proceeding to the development stage. (4) The validity of the frogmath media is in the very good category, and the effectiveness of the frogmath media is in the very effective category.